2020
DOI: 10.1037/abn0000504
|View full text |Cite
|
Sign up to set email alerts
|

Apophenia as the disposition to false positives: A unifying framework for openness and psychoticism.

Abstract: Positive symptoms of schizophrenia and its extended phenotype—often termed psychoticism or positive schizotypy—are characterized by the inclusion of novel, erroneous mental contents. One promising framework for explaining positive symptoms involves apophenia, conceptualized here as a disposition toward false-positive errors. Apophenia and positive symptoms have shown relations to openness to experience (more specifically, to the openness aspect of the broader openness/intellect domain), and all of these constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 57 publications
4
56
0
Order By: Relevance
“…Additionally, positive schizotypy was associated with the self-reported tendency to experience coincidences in one’s life as meaningful (Rominger et al, 2018). Another study found that positive schizotypy was associated with false positives on a semantic association task, such that participants high in positive traits were more likely to label unrelated item pairs as related (Blain et al, 2019). Experience sampling studies have captured subjective reports of altered experience of salience in real-world settings.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, positive schizotypy was associated with the self-reported tendency to experience coincidences in one’s life as meaningful (Rominger et al, 2018). Another study found that positive schizotypy was associated with false positives on a semantic association task, such that participants high in positive traits were more likely to label unrelated item pairs as related (Blain et al, 2019). Experience sampling studies have captured subjective reports of altered experience of salience in real-world settings.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the Big Five traits can be thought of as relating to particular motivational, cognitive, and affective mechanisms (DeYoung, 2015;. For example, pattern detection and curiosity for Openness-Intellect (Blain, Longenecker, et al, 2020;DeYoung et al, 2012) and reward sensitivity for Extraversion (Blain, Sassenberg, et al, 2020;Smillie et al, 2012). Agreeableness appears to reflect tendencies related to navigating social norms and coordinating with the needs of others (DeYoung, 2015;DeYoung & Weisberg, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Assessing variables of interest at the latent level allows for more robust conclusions, as latent variables capture only the shared variance of their indicators, thereby eliminating unsystematic error variance and more accurately capturing variability in the underlying constructs of interest (Keith, 2006). Single-task performance-based indicators are often limited in their scope and measure constructs narrower than those they purport to represent (Apperly, 2012;Blain, Longenecker et al, 2020). Performance on any given task is influenced by a number of task-specific factors, but using multi-indicator designs and latent variable frameworks allows us to move toward measuring constructs more reliably as what is shared across multiple tasks, thereby avoiding underestimation of true effect sizes (Blain, Longenecker et al, 2020;Enkavi et al, 2019;Eisenberg et al, 2019;Campbell & Fiske, 1959;Nosek & Smyth, 2007).…”
Section: Utility Of Latent Variable Modelingmentioning
confidence: 99%
See 2 more Smart Citations